Bifunctional HfOx-based Resistive Memory: Reprogrammable and One-Time Programmable (OTP) Memory. (1st June 2022) - Chen, Ying-Chen; Chang, Yao-Feng; Lin, Chao-Cheng; Lin, Chang-Hsien
Abstract : The dual functions in HfOx -based ReRAM and 2V-programmable via-fuse technology featuring in simple metal-insulator-metal BEOL process are presented, which can integrate with the current metal fuse technology. The impact of via-size, ReRAM, and via-fusing programming windows, stacked structures, and integration capability has been extensively studied. The performance and reliability risk assessments show that the ReRAM and via fuse can sustain at 438 K for 500 h without any degradation. Our results provide pathfinding of high density, integration capability, low programing voltage, multi-functionality between programmable read-only memory (PROM) and ReRAM co-existing in embedded applications.